UJI IN-VITRO ANTIBAKTERI EKSTRAK ETIL ASETAT DAUN KELAKAI (STENOCHLAENA PALUSTRIS (BURM.F.) BEDD.) TERHADAP BAKTERI PENYEBAB DIARE ESCHERICHIA COLI DAN SALMONELLA TYPHI - Siti Saniah; Dinda Puspita Sari; Amar Abdat; Senponi Pebriani; Muhammad Hery Dayesdha Yade; Jordi Setiawan; Erlina Fatmasari (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2023)
Kelakai (Stenochlaena palustris (Burm. f.) Bedd.) one of the typical plants of South Kalimantan which has many benefits, not only often consumed as food, also useful as treatment, which is diarrhea disease. This study aims to determine the standardization of simplisia and phytochemical screening of ethyl acetate extract of kelakai leaves and in-vitro antibacterial tests against bacteria cause diarrhea e.coli & salmonella typhi. The research method begins with the preparation of simplisia, ethyl acetate extract of kelakai leaves, in-vitro antibacterial testing against bacteria cause diarrhea e.coli & salmonella typhi with a concentration variation of 12.5%; 25%; 37.5% & 50%. The results obtained on kelakai leaf simplisia are drying shrinkage with an average 7.5%. Water soluble juice content with an average 24% and ethanol soluble juice content with an average 19%. Phytochemical screening of ethyl acetate extract of kelakai leaves is positive for alkaloids, tannins, phenols, saponins, and flavonoids. This study shows antibacterial activity against bacteria that cause diarrhea, namely e.coli and salmonella typhi, has good potential with a concentration of 12.5% as seen from the diameter of the inhibition zone formed including the medium category, which is 10.18 mm in salmonella typhi bacteria and 10.86 mm in e.coli bacteria